Primary Malignant Melanoma Limited to the External Auditory Canal: A Rare Presentation - Samal, Dillip Kumar; Preetam, C.; Sahoo, Anjan Kumar (Annals of Otology and Neurotology, 2021)
Malignant melanoma limited to the external auditory canal is very rare. These patients present relatively late as compared with melanoma involving other subsites of external ear. However, the tumor is slow-growing but shows aggressive behavior with a poor prognosis when presented late. We have a 44-year-old female who presented with a blackish lesion, which was bleeding on and off from her left ear. She was managed with wide local excision, preserving maximum part of external auditory canal cartilage. The histopathology of the lesion was suggestive of malignant melanoma. After a thorough evaluation, she was kept under close follow-up. Malignant melanoma of external auditory canal shows poor prognosis usually, mainly because of late presentation. Thus, early diagnosis is crucial, as in our case, where wide local excision was sufficing, and the patient is disease-free after 4 years of follow-up.
Keywords: superficial parotidectomy; lateral temporal bone resection; neck dissection; external auditory canal